2022
DOI: 10.1155/2022/3553617
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Oxidative Stress and Exosomes

Abstract: Mammals have several organs comprising various cells with different functions. Furthermore, eukaryotic cells are compartmentalized into functionally distinct organelles. Thus, for good organismal health, exosomes, which play an important role in cell-to-cell communication, interact closely with oxidative stress. Oxidative stress, which is recognized as a type of intracellular second signal, is aggravated by reactive species. As a subtype of reactive species, reactive oxygen species (ROS) can be produced on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…Our study showed the antioxidant e cacy of ADSC exosomes in recipient keratinocytes, consistent with previous ndings. The antioxidant effects of MSC-derived exosomes are thought to involve the transfer of antioxidative enzyme mRNA, proteins, or miRNAs into recipient cells [39]. MSC-derived exosome therapy offers several advantages over stem cell transplantation itself [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the antioxidant e cacy of ADSC exosomes in recipient keratinocytes, consistent with previous ndings. The antioxidant effects of MSC-derived exosomes are thought to involve the transfer of antioxidative enzyme mRNA, proteins, or miRNAs into recipient cells [39]. MSC-derived exosome therapy offers several advantages over stem cell transplantation itself [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL-1ÎČ may induce hyperglycolysis in multiple cells [ 33 ]. It must be noted that IL-1ÎČ can induce elevated superoxide formation via activation of NADPH oxidases, since ROS can be produced not only via the mitochondrial electron transport chain but also via NADPH oxidases [ 34 ]. Moreover, a drop in the Διm is a distinguishing mark of apoptotic cell death [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, OS can notably affect the number of exosomes by regulating the degradation of multivesicular bodies. High levels of OS promote the degradation of intracellular multivesicular bodies by activating autophagy, lessening the amount of exosomes, thereby influencing exosome function, reducing the antioxidant effect of exosomes, and exacerbating the damage of OS on oocytes (201). Qu et al determined that human umbilical cord MSC-derived exosomes carrying miR-126-3p promoted angiogenesis in POI rats and attenuated apoptosis of ovarian GCs, highlighting the potential of miR-126-3p-containing exosomes as an effective therapeutic strategy for POI treatment (202).…”
Section: Os-mediated Exosomes In Poimentioning
confidence: 99%